2007
DOI: 10.1089/sur.2006.049
|View full text |Cite
|
Sign up to set email alerts
|

Video-Thoracoscopic and Open Surgical Management of Thoracic Empyema

Abstract: Many treatment modalities are available for thoracic empyema, depending on the results of appropriate clinical and laboratory investigations. In fibrinopurulent empyema, VATS debridement is safe and effective, with minimal morbidity and no deaths. Lung decortication via thoracotomy is the only option for organized empyema and is associated with a substantial mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…83 Thoracotomy remains the main salvage procedure after unsuccessful thoracoscopy, as defined by the failure of lung expansion to the chest wall. 62,72,84 Performed in appropriate operative candidates, the . A patient with a chronic left-sided empyema and bronchopleural fistula due to recurrent pneumonia underwent drainage of pleural pus with a large-bore chest tube.…”
Section: Thoracotomy Decortication and Open Drainagementioning
confidence: 99%
“…83 Thoracotomy remains the main salvage procedure after unsuccessful thoracoscopy, as defined by the failure of lung expansion to the chest wall. 62,72,84 Performed in appropriate operative candidates, the . A patient with a chronic left-sided empyema and bronchopleural fistula due to recurrent pneumonia underwent drainage of pleural pus with a large-bore chest tube.…”
Section: Thoracotomy Decortication and Open Drainagementioning
confidence: 99%
“…Various studies have implied that thoracotomy and open surgery is an acceptable treatment in patients with stage 3 empyema, due to increased technical failure of VATS. 1,5,11 However, the results of VATS in this phase have also been reported. Studies comparing VATS to open surgery in patients with chronic empyema (stage 3) found less postoperative chest drainage, shorter hospital stay, less pain after the operation, and earlier mobilization after VATS.…”
Section: Discussionmentioning
confidence: 99%
“…Initially VATS was used for diagnostic purposes and confirmed the presence of empyema [6]. Later VATS debridement was found to be a very effective method of treating early fibrinopurulent empyema [7,8]. The reduced morbidity and more pleasing aesthetics associated with a VATS approach generated great interest in the procedure.…”
Section: Video-assisted Thoracoscopic Surgerymentioning
confidence: 99%